3-Monochloropropane-1, 2-diol causes irreversible damage to reproductive ability independent of hormone changes in adult male rats. (February 2019) - Xing, Han-Zhu; Fang, Bing; Pang, Guo-Fang; Ren, Fa-Zheng
Abstract: 3-MCPD, a contaminant frequently detected in foodstuffs, has been reported to damage human kidneys and testes. Previous studies can be used to evaluate the risk to humans of exposure to excessive 3-MCPD for a short period. However, the effects of withdrawal after 3-MCPD exposure have rarely been studied. Adult male SD rats were orally administered 0, 36 and 72 mg 3-MCPD/kg b.w./day for 4 weeks, followed by a 7-week recovery period. 3-MCPD significantly reduced RBC, HGB and HCT levels, indicating a phenotype of anemia, which returned to normal after the recovery period. 3-MCPD induced dysfunction in the liver and kidneys, which were characterized by hepatomegaly and elevated serum ALT, TBIL levels, and nephromegaly and elevated serum urea, UA contents. These effects were also restored to normal after the recovery period. Although the abnormal levels of testosterone and progesterone returned to normal, 3-MCPD-induced atrophy in testes, decreased sperm concentration and motility, and an increased rate of teratosperm still existed after the recovery period. 3-MCPD can induce restorable anemia and dysfunction in liver and kidney but irreversibly damage the reproductive system with normal sex hormone levels. This study may provide a novel perspective for characterizing the ongoing risk of exposure to 3-MCPD. Highlights: 3-MCPD induced anemia and damages in liver and kidney can be recovered. The disturbed testosterone and progesterone induced by 3-MCPD was recoverable. 3-MCPD caused irreversible decrease in the concentration and activity of sperm. The atrophy and damage of testes and epididymis induced by 3-MCPD was irreversible.